2018
DOI: 10.18203/2394-6040.ijcmph20183974
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study to assess the health profile of street sweepers and sanitary workers in a zone of Greater Chennai Corporation, Tamil Nadu, India

Abstract: Background: Sweepers and sanitary workers are getting exposed to hazardous dust during their work. The health profile of the sanitary workers and utilization of health services are not clearly known. This study aimed to assess the health profile and associated risk factors among street sweepers and sanitary workers.Methods: A community based cross sectional study was conducted among 73 street sweepers and sanitary workers in a zone of Greater Chennai Corporation by multistage sampling method, during November 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The reason being exposed this much might be the duration of time that they spent more time working on municipal solid waste collection activities. Similarly, studies conducted in Tamil Nadu, India 1 and Bahir Dar and Gondar town 21 showed that working hour per day was significantly associated with occupational health symptoms. Municipal solid waste collectors who had work experience greater than 5 years were 1.68-times more likely to have occupational health symptoms compared to those who had work experiences of five or less than five years.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The reason being exposed this much might be the duration of time that they spent more time working on municipal solid waste collection activities. Similarly, studies conducted in Tamil Nadu, India 1 and Bahir Dar and Gondar town 21 showed that working hour per day was significantly associated with occupational health symptoms. Municipal solid waste collectors who had work experience greater than 5 years were 1.68-times more likely to have occupational health symptoms compared to those who had work experiences of five or less than five years.…”
Section: Discussionmentioning
confidence: 88%
“…The occupational health symptoms due to the absence of using a full body suit PPE were higher compared to the study done in Bahir-Dar city and Gondar town, 21 but it was lower compared to the study done in Addis Ababa before 7 years and in Tamil Nadu, India, a study among street sweepers and sanitary workers. 1 Municipal solid waste collectors who worked more than 8 hours per day were 1.81-times more likely to have occupational health symptoms compared to those who worked 8 or less hours per day. The reason being exposed this much might be the duration of time that they spent more time working on municipal solid waste collection activities.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…problems reported due to waste handling. 32 Attack by animals during work was also reported among municipal SW workers 21,31 and rag pickers. 28,33 A study among the municipal SW workers in Chennai had 3.3 times the odds of having respiratory morbidity than the control group 25 and it was 4.24 times among sweepers in Nagpur than a control group of Class IV workers in the office buildings.…”
Section: Documented Various Types Of Dermatologicalmentioning
confidence: 94%
“…[28][29][30] High prevalence of skin infections among SW workers was seen in a study 12 compared to a few other studies. 20,31 Nayak. et al,…”
Section: A Pool Of Health Morbidities Among Sw Workersmentioning
confidence: 99%